Electronic Coconut Scraper Machine / Norhafizah Ab Jalil - Ab Jalil, Norhafizah (2020)
H&H Enterprise is has opened on 20th February 2018 and the location is located at Pekan, Pahang. My business type is a single proprietorship since the business is owned by myself. H&H company is focusing on providing the new innovative products to the loyal consumer of my product. My company has an action plan for getting the goals which are focusing to be “the best” and inspires my business to move forward. Then, produce products and service that consistently achieved the quality and serving expectation of the customer.